Efficacy of New Mindfulness-Based Swinging Technique Intervention: A Pilot Randomised Controlled Trial Among Women With Breast Cancer - Bahcivan, Ozan; Estapé, Tania; Gutierrez-Maldonado, Jose (Frontiers in Psychology, 2022)
Objective Combining 3rd-wave-therapies with Cognitive-Behavioural-Therapy (CBT) has increased in recent years. Usually these therapies require longer sessions which therefore increases the psychotherapy drop-out rate for cancer patients for multiple medical reasons. This inspired intervention of a shorter 20 min-long mindfulness-therapy (MBST) to be developed for Breast-Cancer-patients (BC). Method This pilot randomised controlled trial was to assess the immediate-outcome of the MBST-intervention for its efficacy for BC-patients by using the Pearson Chi-square test, Fisher–Freeman–Halton exact test, and McNemar test for categorical variables; Mann–Whitney U and Wilcoxon test for the continuous variables. The Emotion Thermometer, State Trait Anxiety Inventory, Hospital Anxiety and Depression Scale, Self-Efficacy for Managing Chronic Disease, and Beck’s Hopelessness Scale were used for measuring the intervention outcomes. One hundred seventy-three BC patients were randomly assigned in two-groups (equal-mean-age, p = 0.417). Control-Group (CG, n = 82) received cognitive-disputation-technique a form-of-CBT, and Intervention-Group (IG, n = 74) received MBST. The directives are given to IG: psychoeducation about Mindfulness, and to imagine themselves swinging-in a peaceful environment. When the patients imagine their swing going up, they physically take a deep-breath, and when going down they physically release their breath, and this process is repeated. Result Outcomes post-treatment showed significant higher-improvement in IG in all the assessed-measurements, with large-effect-size: anxiety (p < 0,05, r = 0,67) and depression-levels (p < 0,05, r = 0,71); anxiety-trait (p < 0,05; r = 0,79) reduced, it increases self-efficacy for managing-disease (p < 0,05, r = 0,82) as-well-as hopefulness (p < 0,05, r = 0,61) and saturation-level measured by pulse-meter/oximeter (p < 0,05, r = 0,51). Conclusion MBST is an efficacious intervention to reduce psychotherapy session time for immediate relief from clinical anxiety and hopelessness as well as increase self-efficacy and improve tranquillity for BC-women. It may have a particular clinical significance for supporting patient’s adherence to treatment. Although in this pilot sample MBST was found to be effective for short-term-outcome, its efficacy for longer-term-outcome should be examined in future trials. Additionally, breathing laps can be increased possibly for a greater result on rise of saturation levels of patients.